Analyze the Effects of Fast Food on the Health of College Going Students - Saira Abbas, Madiha Naz, Syed Muhammad Ahmad Gillani, Saima Afzal, Norina Jabeen, Adeela Manzoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Fast food is a major part of our present life, due to some factors such as the style of life, value and the huge commercial advertisements, it has several effects on human health. Objectives: The basic purpose of this study was to identify the effects of fast food on the health of college-going students. Material and methods: Mixed method research is used for data collection. For qualitative data, 4 key informant interviews were conducted. For quantitative data, a descriptive research design was used and random sampling techniques were selected for sample size. The sample size consisted of 107 respondents. A guideline questionnaire was used for key informants as well as a well-structured questionnaire was used for the purpose of data collection. For analysis of qualitative data thematic analysis was used. Statistical packages for social sciences (SPSS) were used for quantitative data analysis. Results: The main effects of fast food on the health of college-going students like heart problems, obesity, fat, sugar and blood pressure. Majorities (91.6%) of the respondents have information about fast food and (8.4%) did not have any information about fast food disease. A majority (77.6%) of the respondents have information about the controlled use of fast food and 22.4% did not know it. Conclusion: Mass media should spread awareness among students about the side effects of fast food. So, it is a dire need of time to create awareness among the society at youngsters’ level and nutrition programs should be studied as well as the role of mass media should be changed for creating awareness regarding the effects of fast food.